Efek Toksisitas Akut Ekstrak Daun Paku Sisik Naga (Drymoglossum piloselloides (L.) Presl) terhadap Nilai Darah Mencit Putih (Mus musculus L.) - - Yuliastuti; Resti Rahayu; - Efrizal (Jurnal Biologi Universitas Andalas, 2014)
The acute toxicity effects of leaf extract of dragon scales fern (Drymoglossum piloselloides (L.) Presl) on hematological values of male albino mice (Mus musculus L.) has been tested at the Laboratory Animal Physiology. The experiment tested extract dose from 50 to 200 mg/Kgbw on hematological values of male albino mice. The treatments  used a randomized block design method. The mice were injected by the leaf extract at several doses: i.e.  0 mg/Kgbw, 50 mg/Kgbw, 100 mg/Kgbw, 150 mg/Kgbw and 200 mg/ Kgbw. The blood were collected at 24 hours after treatment and hematological values have been examined including number of red and white blood cell, hematocrite, hemoglobin concentration (Hb), plasm protein concentration, absolute blood indices, diameter and morphology of eritrocyte. The results showed that the leaf extract of D. piloseloides gave no acute toxicity effect of hematological values.Keywords: Drymoglossum piloselloides, hematology, acute toxicity